Bahasa Inggris - Muhammadi; Aditra Zulfi; Nabela Ayu (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop valid, practical, and effective Macromedia Flash-based interactive multimedia to improve elementary school students’ computational thinking skills on the topic of Indonesian Cultural Wealth. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants were fourth-grade students of SDN 05 Sawahan and SDN 01 Sawahan, Padang Timur District. The results showed that the developed multimedia was highly valid, with validation scores of 90.48% from material experts, 90.79% from language experts, and 87.50% from media experts. The practicality test indicated very practical criteria, with teacher and student response scores of 89.28% and 91.08%, respectively. The effectiveness test revealed a significant difference between pretest and posttest scores in the experimental class (t = 15.499 > 1.711; Sig. = 0.000 < 0.05), indicating an improvement in students’ computational thinking skills. The N-gain results were 0.64 for the experimental class and 0.48 for the control class, both categorized as medium. The novelty of this study lies in the integration of computational thinking components—decomposition, pattern recognition, abstraction, and algorithmic thinking—into interactive multimedia through animations, simulations, and educational games tailored to elementary school students. Therefore, the developed multimedia can serve as an effective learning medium in elementary education.